Veterinary medicinal products to control Varroa destructor in honey bee colonies (Apis mellifera) and related EU legislation – an update. Issue 1 (1st January 2016) - Mutinelli, Franco
Abstract : An update is provided on authorised veterinary medicinal products to control Varroa destructor infestation of the honey bee ( Apis mellifera ) in the European Union and Switzerland. An assessment is made of current European Union legislation, authorisation procedures and the availability of veterinary medicinal products. Concerns related to authorisation procedures and the availability of veterinary drugs are discussed from simplifying procedures and making veterinary medicinal products more widely available amongst the member states.